Building Commitment to Reform through Strategic Communication : The Five Key Decisions - Cabanero-Verzosa, Cecilia (World Bank, 2012)
This workbook gives the reader a management decision-making tool for developing a communication strategy that will support a proposed reform. This decision tool helps a reform project team focus its efforts by disciplining it to select only those communication activities that will prompt its target audiences to learn new information and adopt positive attitudes that lead to desired changes in behavior. The decision-making approach described here also helps program manager's work more effectively with communication specialists. This tool has been used by program managers in developing countries and taught at workshops and in formal courses conducted face-to-face; by videoconference; and through self-paced, computer-based modules. To illustrate how this tool may be used in various types of development activities and in diverse settings, the authors provide examples drawn from projects, economic and sector work, country assistance strategies formulated by donor groups, and country programs designed by developing-country government teams to reduce poverty.